Tuning Light‐Driven Water Oxidation Efficiency of Molybdenum‐Doped BiVO4 by Means of Multicomposite Catalysts Containing Nickel, Iron, and Chromium Oxides. Issue 2 (12th February 2020) - Krysiak, Olga A.; Junqueira, João R. C.; Conzuelo, Felipe; Bobrowski, Tim; Wilde, Patrick; Wysmolek, Andrzej; Schuhmann, Wolfgang
Abstract: Mo‐doped BiVO4 has emerged as a promising material for photoelectrodes for photoelectrochemical water splitting, however, still shows a limited efficiency for light‐driven water oxidation. We present the influence of an oxygen‐evolution catalyst composed of Ni, Fe, and Cr oxides on the activity of Mo:BiVO4 photoanodes. The photoanodes are prepared by spray‐coating, enabling compositional and thickness gradients of the incorporated catalyst. Two different configurations are evaluated, namely with the catalyst embedded into the Mo:BiVO4 film or deposited on top of it. Both configurations provide a significantly different impact on the photoelectrocatalytic efficiency. Structural characterisation of the materials by means of SEM, TEM and XRD as well as the photoelectrocatalytic activity investigated by means of an optical scanning droplet cell and in situ detection of oxygen using scanning photoelectrochemical microscopy are presented. Abstract : Important interfaces : The performance of catalyst‐modified photoanodes depends not only on the nature of the catalyst but is strongly determined by the formed interface between photoabsorber and catalyst. As a result, the activity of the photoanodes may substantially vary if a given catalyst is located on top or is embedded within the photoabsorber layer.